2016
DOI: 10.4995/var.2016.5864
|View full text |Cite
|
Sign up to set email alerts
|

BIM Open Source Software (OSS) for the documentation of cultural heritage

Abstract: Abstract:The Building Information Modelling (BIM) software enables the users to communicate and design, understand appearance, performance and cost in the spatial and urban design process. Another important use of the BIM technology is the documentation and 3D reconstruction of cultural heritage monuments. The appropriate BIM software equips the users with tools to easily capture and analyse concepts and maintain the coordination of design data through documentation and 3D modelling. Many developments come up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 10 publications
0
28
0
5
Order By: Relevance
“…Starting from the 90s (Forte and Siliotti, 1997) the use of 3D computer graphics in relation with archaeology and cultural heritage has been a focus of attention for scholars in multi-disciplinary fields. An abundance of publications have emerged in the last two decades which have presented photo-realistic reconstructions of the past (Logothetis et al, 2016) and (Manferdini et al, 2016). This stream continues to make contributions to the creation of a new legacy in cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the 90s (Forte and Siliotti, 1997) the use of 3D computer graphics in relation with archaeology and cultural heritage has been a focus of attention for scholars in multi-disciplinary fields. An abundance of publications have emerged in the last two decades which have presented photo-realistic reconstructions of the past (Logothetis et al, 2016) and (Manferdini et al, 2016). This stream continues to make contributions to the creation of a new legacy in cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey showed that there is no available, wellrespected and comprehensive FOSS BIM platform to be used for the overall cultural heritage documentation project. The lack of such a (FOSS) platform persistently outlines the real need for the development of plug-ins in different areas of the BIM software, which could be freely available to a large community of professional designers, architects, engineers and conservators but also for the research community for applied research (Logothetis and Stylianidis, 2016).…”
Section: Scan To Bim Add-onmentioning
confidence: 99%
“…Many users prefer commercial software BIM instead of FOSS because there is not a credible and comprehensive platform that can be used for the overall 5D digital representation of a building. There are only a few, accessible and free BIM viewers to visualise the final produced model (Logothetis and Stylianidis, 2016), as presented previously in Table 1.…”
Section: Foss Cad and Foss Bimmentioning
confidence: 99%
“…This characteristic will allow for the useful data to be recovered at any time, avoiding time wasting and reducing the possibility of errors [74]. The collaborative work is possible thanks to the interoperability of BIM platforms, which is achieved by the development of an open and standardized data structure (standard: ISO 16739), called Industry Foundation Classes (IFC) [19].…”
Section: Building Information Modeling (Bim) Approachesmentioning
confidence: 99%